Estudo sobre a potencialidade melancólica - Moser, Matheus (2012)
The present research consists in a study about the melancholic potentiality. The subject of this study is the actress Marilyn Monroe (1926-1962) whom, based in her biography, I suppose to be a carrier of a melancholic potentiality because of the exhibition of a series of melancholic features and for have suffered a narcissistic disqualification in the primordial moments of the constitution of her psyche. The objective of this study is to make a psychopathologic read of the case, prioritizing the identity conflict of Marilyn Monroe. The psychoanalysis is the theory used in this work, which has as principal authors Freud, Aulagnier and Violante